APPLICATION OF ARBUSCULAR MYCORRHIZAL INOCULUM IN GREENHOUSE SOIL WITH MANURE INDUCED SALINITY FOR ORGANIC PEPPER PRODUCTION - Nikolaos Kapoulas; Zoran S. Ilić; Athanasios Koukounaras; Ioannis Ipsilantis (Acta Scientiarum Polonorum: Hortorum Cultus, 2019)
In this study, the effect of arbuscular mycorrhizal fungus − AMF Rhizophagus intraradices inoculum (prior or with transplanting) to different pepper type (Capsicum annuum L.) cv. Arlequin F1 (long fruits) and Raiko F1 (bell pepper), on plant growth and physiological parameters in response to elevated soil P concentrations from organic greenhouse production with enhanced soil salinity, was investigated. To explain the physiological growth of mycorrhizal inoculated (M) and non-mycorrhizal inoculated (NM) plants, the parameters of fungal root length colonization, shoot concentration of P an N during growth, plant height, width of stem, yield, number of fruit per plant and also the quality parameters of fruits such as soluble solid content (SSC), fruit color, mineral profile, total soluble phenolics (TSP) and antioxidant activity (FRAP), were determined. This study showed that application of AMF in cv. Raiko cultivated in high P saline soil generally enhanced growth, fruit yield and number of fruits per plant when inoculated at planting time in the greenhouse. AM inoculated plants, regardless of the time of application in cv. Arlequin grown under the same conditions, did not have any significant differences in comparison with NM plants. Arbuscular mycorrhizal inoculation has great potential in enhancing the pepper growth and yield even in high soil P, however, because of the complexity and interaction of involved genotypes of pepper and AMF, the method and time of inoculation, the system of pepper production and environmental conditions, as well as assays have to be performed to verify positive effects.